Tweeting from Gezi Park: Social Media and Repression Backfire. (August 2018) - Odabaş, Meltem; Reynolds-Stenson, Heidi
We examine how social media may facilitate protest mobilization in response to violent state repression. Prior research demonstrates that violent repression can either decrease protest participation through raising the costs of participation, or can generate outrage, resulting in "backfire" and an increase in mobilization. Many recent mass mobilizations have garnered attention from scholars and journalists alike due to the instances of repression backfiring as well as the widespread use of social media in these protest movements. We examine why these two trends may be related using logistic regression analysis on data on participants in the Gezi Park Protests in summer 2013. Controlling for confounding factors, we find a statistically significant relationship between being recruited to participate in the protests through social media and joining the mass mobilization as a reaction to police repression. We argue that in the case of Gezi Park, communication through social media was a key factor in facilitating social movement mobilization in response to repression.